2020
DOI: 10.5551/jat.53447
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Seaweed Intake and Its Association with Cardiovascular Disease Mortality: The JACC Study

Abstract: Seaweed is a popular traditional foodstuff in Asian countries. To our knowledge, few studies have examined the association of seaweed intake with mortality from cardiovascular disease. We examined the association of frequency of seaweed intake with total and specific cardiovascular disease mortality. Methods: We examined the association of seaweed intake with mortality from cardiovascular disease among 40,234 men and 55,981 women who participated in the Japan Collaborative Cohort Study for Evaluation of Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…In our study, the average intake of seaweed was 2.8 g/d, which is lower than the previous studies performed in Japan (9.9 g/day) and Korea (8.5 g/day) 36,37 . Moreover eating habits may vary greatly in different areas of China.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In our study, the average intake of seaweed was 2.8 g/d, which is lower than the previous studies performed in Japan (9.9 g/day) and Korea (8.5 g/day) 36,37 . Moreover eating habits may vary greatly in different areas of China.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous epidemiologic studies have shown the potential benefits of seaweed for cancer, CVD and diabetes 36‐38 . Studies have also investigated the association between seaweed and MetS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, seaweed is rich in bioactive compounds, such as polyphenols and carotenoids [3]. Recent epidemiological evidence indicates that a seaweed intake is associated with a reduced incidence of cardiovascular disease mortality and increased life expectancy [4,5]. Seaweed has been regularly consumed in the daily diet since ancient times in Japan, Korea, and China, which may contribute to the longevity noted in these countries [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the reproducibility of seaweed intake in the 24 h dietary recall survey was not high (quadratic weighted kappa coefficient 0.24, Spearman's correlation coefficients 0.14) compared with the reproducibility estimated by using repeated food frequency questionnaires in the other study 23) (Spearman's correlation coefficients 0.35). In previous studies, the frequency of seaweed intake was usually one to two times or three to four times a week 22,23) ; therefore, the participants may not necessarily have consumed seaweed the day before the survey. Since such measurement errors would occur randomly across the exposure groups, they likely diluted the association between seaweed intake and risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The Japan Public Health Center (JPHC) Study, involving 86,113 men and women aged 40-69 years during the baseline period (1990)(1991)(1992)(1993)(1994), showed that the frequency of seaweed intake was inversely associated with the risk of incident coronary heart disease among men and women but not of stroke 23) . By contrast, another recent report from the Japan Collaborative Cohort (JACC) Study, involving 96,215 men and women aged 40-79 years during the baseline period (1988)(1989)(1990), showed that the frequency of seaweed intake based on a food frequency questionnaire was inversely associated with mortality from total stroke, cerebral infarction, and total cardiovascular disease among women but not among men 22) . In that study, seaweed intake was not associated with mortality from coronary heart disease in either sex.…”
Section: Follow-up and Determination Of Ischemic Cardiovascular Diseasementioning
confidence: 92%